Social Network and Social Force - Phetcharaburanin, Prisana (Journal of Advanced Development in Engineering and Science, 2023)
Social network like the big mirror that represents user?s inner thought which can not reveal in real life. The idea of social network may affect the idea of society. Thai social network also expands and has more roles in Thai Society in the last decade. Thai social network represents their social force many times as well as other countries. However, some people believe that social network may not have as much social force as a lot people think. One of the biggest obstacles is that people need close their personal connections in order to get them to take action. They will never reveal their personal connections in risky and hard action Social revolution need more social force from many varieties of social groups instead of using just only social force from social network.